A major selection problem. Issue 6 (December 2016) - Jones, Corey; Garwood, Kathleen Campbell; Strandberg, Alicia Graziosi
Abstract : Corey Jones, Kathleen Campbell Garwood and Alicia Graziosi Strandberg dig into US Census data to investigate the gender pay gap, and the gender imbalance in college major enrolments. Abstract : Corey Jones, Kathleen Campbell Garwood andAlicia Graziosi Strandberg dig into US Census data to investigate the gender pay gap, and the gender imbalance in college major enrolments